Immediate versus deferred treatment for early prostatic cancer. Issue 746 (December 1987) - Smith, P. H.; Armitage, T. G.
Abstract : The diagnosis of early (non-metastatic) prostatic cancer is dependent upon the patient presenting himself with symptoms or for routine rectal examination or ultrasound screening. Diagnosis in the absence of symptoms is more common outside the United Kingdom and as a result the opportunity to treat such patients occurs more commonly in other countries. The treatment options for the different stages are reviewed and the evidence for their effectiveness is considered. A review of the literature yields conflicting evidence of the efficacy of and the necessity to institute early therapy. This basic gap in our current knowledge should be filled when the results of the existing Medical Research Council (MRC) clinical trial of immediate and deferred orchidectomy are available.